The Implementation of National Standard-Based Curriculum in Private Islamic Higher Education: Leadership Impact - A. Rusdiana; Nasihudin Nasihudin (Jurnal Pendidikan Islam, 2018)
The implementation of KKNI (Kerangka Kualifikasi Nasional Indonesia/national standard–based curriculum), especially in PTKIS (Perguruan Tinggi Keagamaan Islam Swasta/Private Islamic Higher Education) demands the role of its study program leaders. The purpose of this study was to explore the implementation of KKNI curriculum on several perspectives: role, performance, teaching steps, understanding factors related to the distribution KKNI, and impact to education in Indonesia. This study used a descriptive qualitative method, including interview, observation, and documentation as technique for collecting data and triangulation technique for ensuring data validity. The results indicated that the performance of eight heads of PAI (Pendidikan Agama Islam/Islamic education) Study Program was not in optimum condition as a determinant of the direction, representative of spokesperson, communicator, mediator, and integrator. The implementation of the curriculum was also not effective yet. Then, the factors that influence the implementation are the lack of resources, time, campus ethics, knowledge support, professional interests and attitudes. To understand this condition, we also investigated the impact of knowledge, in which the result showed no information regarding what the policy/program offers, what the target group needs, and why the average student's score is still low. National accreditation, in the eight PAI Study Programs, did not reach the excellence category. Thus, the performance on the study program has not been accountable and will have implications for the weakness of social legitimacy.